Predicting the long-term performance of a geogrid-reinforced embankment on soft soil using two-dimensional finite element analysis - Karim, M.R.; Manivannan, G.; Gnanendran, C.T.; Lo, S.C.R. (2011)
The consolidation of the soft foundation soil of a geogrid-reinforced embankment, improved with prefabricated vertical drains (PVDs), is modelled in this paper using two-dimensional (2D) plane strain coupled finite element (FE) analysis to predict long-term multiple behaviour characteristics (e.g., settlement, lateral displacement, excess pore-water pressure response, geosynthetic strain) of the embankment. Two sets of analyses were carried out with the foundation soil being modelled using relatively simple elastic-viscoplastic (EVP) models. A nonlinear creep function was used in association with them. The input material parameters were determined from extensive laboratory testing or were taken from reliable sources except for the horizontal permeability, which was systematically back-estimated using oedometer test data and the first year of field settlement data. The results from both analyses were compared with the long-term (up to 6 years) field-monitoring data and were found to be in good agreement with the field measurements.